2021
DOI: 10.22219/jpbi.v7i1.15510
|View full text |Cite
|
Sign up to set email alerts
|

LARO (Learners Active Response to Operant) lessons in improving the basic science process skills of elementary pupils

Abstract: Science is regularly taught in ways that make the data unessential, theoretical, and disengaged from students' experiences. Although most students do anticipate to learn science, they regularly see it as being presented in uninteresting ways. This study aimed to determine the effectiveness of using LARO (Learners Active Response to Operant) lessons in teaching Science and their roles in promoting students' basic science process skills (BSPS). This action research employed a descriptive research design. Thirty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The same findings by Bete (2020) study revealed a poor process skill in one science class in grade 8 students. Barantes and Tamoria (2021) also revealed the effectiveness of a learning technique to help improve basic science process skills. The researchers find it quite intriguing regarding students' science process skills from this literature, wherein recent studies showed low-performance levels.…”
Section: Students' Level Of Science Process Skills Acquisition and Ac...mentioning
confidence: 99%
“…The same findings by Bete (2020) study revealed a poor process skill in one science class in grade 8 students. Barantes and Tamoria (2021) also revealed the effectiveness of a learning technique to help improve basic science process skills. The researchers find it quite intriguing regarding students' science process skills from this literature, wherein recent studies showed low-performance levels.…”
Section: Students' Level Of Science Process Skills Acquisition and Ac...mentioning
confidence: 99%
“…Additionally, Filipino teachers utilized various modalities to deliver quality science education to students. Some of these were educational games, such as Learners Active Response to Operant (LARO) (Barantes & Tamoria, 2021), Strategic Intervention Material (SIM)-based Instruction (Gabucan & Sanchez, 2021), and ICT integration (Sasota et al, 2021). However, some studies also reveal that students face problems and difficulties with some science concepts in secondary education.…”
Section: Introductionmentioning
confidence: 99%